Phosphorylation of ADP-Glucose Pyrophosphorylase During Wheat Seeds Development - Ferrero, Danisa M. L.; Piattoni, Claudia V.; Asencion Diez, Matías D.; Rojas, Bruno E.; Hartman, Matías D.; Ballicora, Miguel A.; Iglesias, Alberto A. (Frontiers in Plant Science, 2020)
Starch is the dominant reserve polysaccharide accumulated in the seed of grasses (like wheat). It is the most common carbohydrate in the human diet and a material applied to the bioplastics and biofuels industry. Hence, the complete understanding of starch metabolism is critical to design rational strategies to improve its allocation in plant reserve tissues. ADP-glucose pyrophosphorylase (ADP-Glc PPase) catalyzes the key (regulated) step in the synthetic starch pathway. The enzyme comprises a small (S) and a large (L) subunit forming an S2L2 heterotetramer, which is allosterically regulated by orthophosphate, fructose-6P, and 3P-glycerate. ADP-Glc PPase was found in a phosphorylated state in extracts from wheat seeds. The amount of the phosphorylated protein increased along with the development of the seed and correlated with relative increases of the enzyme activity and starch content. Conversely, this post-translational modification was absent in seeds from Ricinus communis. In vitro, the recombinant ADP-Glc PPase from wheat endosperm was phosphorylated by wheat seed extracts as well as by recombinant Ca2+-dependent plant protein kinases. Further analysis showed that the preferential phosphorylation takes place on L subunit, which agrees with the role that it plays in the fine and tissue-specific regulation of the enzyme. Results suggest that the ADP-Glc PPase is a phosphorylation target in seeds from grasses but not from oleaginous plants. Accompanying seed maturation and starch accumulation, a combined regulation of ADP-Glc PPase by metabolites and phosphorylation may provide an enzyme with stable levels of activity. Such concerted modulation would drive carbon skeletons to the synthesis of starch for its long-term storage, which later support seed germination and embryo development.